Do the positions of the impacted third molars affect the preoperative anxiety levels and probable postoperative pain levels of the patients? - Ahmet Taylan Çebi; Metin Berk Kasapoğlu (National Scientific Medical Center, 2021)
Objectives: The aim of this study is to evaluate the effects of the position of the impacted third molar teeth on preoperative anxiety and possible pain levels of patients. Material and Methods: Fifty patients with impacted third molar teeth (full bone retention) in the horizontal and vertical positions were included in the study. Sociodemographic data of the patients were recorded. The patients have watched the impacted third molar surgery videos which were the position of horizontal and vertical. Subsequently, preoperative anxiety levels of patients were evaluated with The Spielberger State-Trait Anxiety Inventory-STAI part of the state anxiety inventory. In addition, pain levels that patients thought they might feel after the surgeries were evaluated with Visual Analogue Scale (VAS). P <0.05 and p <0.001 were considered significant in all statistical analyse. Results: The study included 50 patients (25 males and 25 females) who mean the age of was 21.00 ± 2.08. A statistically significant difference was found between the levels of anxiety created by the positions of the impacted third molar teeth (p<0.001, p<0.05). Anxiety levels were higher in female patients than in men (p<0.001, p<0.05). A statistically significant difference was found between the levels of pain that patients could feel postoperatively and position of third molars (p<0.001, p<0.05). Conclusion: The position of the third molars are associated with anxiety, stress, and postoperative pain in patients undergoing impacted third molar surgery. Addressing these factors preoperatively may reduce anxiety, probable postoperative perception of pain, and provide more positive treatment results.